Health System Governance Performance in Improving Clean and Healthy Living Behaviors in Southwest Papua Province - Salomina, Eltje; Hasniati, ‎; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Clean and healthy living behavior (PHBS) is an effort to increase awareness and education in the community about clean and healthy lifestyles. It is expected that with the implementation of PHBS, the community’s quality of life can improve, avoid various diseases, and create a healthy environment. This study aims to measure the performance of health system governance in efforts to improve PHBS in Southwest Papua Province. A qualitative approach is the method used in this research. Data collection methods include observation, in-depth interviews, and documentation. Data sources consisted of primary and secondary data, while data analysis was conducted using interactive methods. The research informants included all parties who play a role in the promotive and preventive activities of living and clean behavior in Southwest Papua Province. The Health System Governance Performance in Southwest Papua Province shows that improving PHBS still faces various problems and challenges. In terms of responsiveness, local governments have established health counseling and socialization programs, but have not fully reached remote areas. Program effectiveness is still limited due to low community participation and a lack of trained health workers. In terms of efficiency, budget allocations are often not targeted and lack transparency. Accountability is still weak, marked by the lack of open performance reporting and program evaluation.